Mechanical properties of various composition of Aluminum Matrix composite - Kamrosni, Abdul Razak; Mohd Nazree, Derman; Noraziana, Parimin; Rita, Mohd Said (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.